A scoping review of the moral experiences of children with medical complexity in Brazil - Raíssa Passos dos Santos; Mary Ellen Macdonald; Franco Carnevale
ABSTRACT Objectives: The aim of this review was to identify and summarize how the moral experiences of children with medical complexity are being expressed within the Brazilian health-related literature and discuss research gaps and directions for future research. Methods: A scoping review was performed using the methodological framework of Arksey and O'Malley and the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). Systematic searches were conducted on Medline, CINAHL, Scopus, and Embase databases. Articles were included if using qualitative methodologies, having children as participants, and published in Brazil. Results: In total, 6,360 articles were retrieved from databases. Sixteen studies were selected for the analysis. Final considerations: The studies were not primarily focused on children's moral experiences. Yet, the studies demonstrate morally relevant accounts concerning children's capacity to reason and interpret their lived experiences, expressing deep concerns about isolation, suffering, future aspirations, and feelings of normality.